External Fixation in the Emergency Department Is Equally Efficacious to Placement in the Operating Room. Issue 3 (14th September 2018) - O'Donnell, Seth; Shah, Kalpit; Gil, Joseph; Johnson, Joseph; Hayda, Roman; Born, Christopher
Category: Trauma Introduction/Purpose: Pilon and unstable ankle fractures are often treated initially with an external fixator (ex-fix) due to soft tissue concerns. Typically, the second stage involves open reduction internal fixation of the fracture as the definitive management. Ex-fix application in the emergency department (ED) has been described previously. We aimed to determine if an ex-fix applied in the ED would have any difference in rate of ex-fix revision, deep infection, and hospital length of stay when compared to an ex-fix that is applied in the operating room (OR). Methods: This is a retroscpective, case-cohort study performed at an urban, level-1 trauma center. Using CPT codes in our billing database, we identified all patients from 2011-2015 who had operative fixation of pilon (AO classification 43B or 43C) or unstable ankle fractures (AO classification 44C) and had application of an ex-fix (either ED or OR) prior to definitive fixation. Patients with open injury, those placed in ex-fix at outside institutions and those treated definitively with ex-fix were excluded. Results: Ninety-six patients met the inclusion criteria. Average age was 47 years and 54 (56%) were male. Thirty-three patients had ex-fix placed in the OR and 63 patients had ex-fix placed in the ED. Post-surgical complications (prominent implant, nonunion, deep infection, DVT, loss of reduction) were seen in 6/33 in the ED and 8/63 in the OR group (χ 2 =0.44, p=0.51). Deep infections occurred in 2/33 OR ex-fix and 5/63 ED ex-fix patients (χ 2 =0.137, p=0.71, OR= 1.4 [95% CI = 0.25 to 7.5]). Revision ex-fix for loss of reduction was performed 4/33 in the OR group and 10/63 in the ED ex-fix group (χ 2 =0.296, p=0.59). Mean length of stay was 14 days for the OR and 13 days for the ED group (p=0.35). Conclusion: We found no significant difference in post-surgical complications (surgical or infectious) or ex-fix revision rates for an ex-fix placed in ED compared to one placed in the OR. Total hospital days were similar in both groups. Prospective studies are needed to validate this method of provisional stabilization in the ED; however, these results indicate that the ED ex-fix is equally efficacious to an OR ex-fix.